Técnicas utilizadas en la gestión de calidad en la planeación y seguimiento de proyectos en organizaciones de Cali - Colombia - Aristizábal Aristizábal, Sebastián (Universidad de San Buenaventura - Cali, 2017)
This research is part of the project "Techniques used in the management of scope in planning and monitoring of projects in Colombia Cali organizations" Professor Ronald Rojas Alvarado Specialization in Integral Project Management of the University of San Buenaventura Cali. The purpose is to know and identify the various techniques used in quality management in the stages of planning and monitoring of projects in organizations of Cali, Colombia. The data collection was carried out through the generation of a data base physical and digital literature obtained by searching indexed databases, physical and digital postgraduate thesis and consulted internet pages and through the development and implementation of a survey for the identification of skills and tools in the management of projects to 36 people involved in managing projects in organizations established in the city of Cali. After sorting and analyzing information obtained were identified the techniques and tools used in the field of quality in each of the stages of project management, throwing real data on its implementation by those involved in the management of projects on established organizations in the city of Cali - Colombia, which was achieved to conclude that those involved in project management know and have used the seven basic tools of quality (BQ1- BQ7), however other existing tools are little known and as a result very little employed in the management of quality in the stages of planning and monitoring of projects.